The ratios of central venous to arterial carbon dioxide content and tension to arteriovenous oxygen content are not associated with overall anaerobic metabolism in postoperative cardiac surgery patients - Abou-Arab, Osama (PLoS One, 2018)
BACKGROUND: The aim of the present study was to evaluate the ability of the ratios of central venous to arterial carbon dioxide content and tension to arteriovenous oxygen content to predict an increase in oxygen consumption (VO(2)) upon fluid challenge (FC). METHODS AND RESULTS: 110 patients admitted to cardiothoracic ICU and in whom the physician had decided to perform an FC (with 500 ml of Ringer's lactate solution) were included. The arterial pressure, cardiac index (Ci), and arterial and venous blood gas levels were measured before and after FC. VO(2) and CO(2)-O(2) derived variables were calculated. VO(2) responders were defined as patients showing more than a 15% increase in VO(2). Of the 92 FC responders, 43 (46%) were VO(2) responders. At baseline, pCO(2) gap, C(a-v)O(2) were lower in VO(2) responders than in VO(2) non-responders, and central venous oxygen saturation (ScvO(2)) was higher in VO(2) responders. FC was associated with an increase in MAP, SV, and CI in both groups. With regard to ScvO(2,) FC was associated with an increase in VO(2) non-responders and a decrease in VO(2) responders. FC was associated with a decrease in pvCO(2) and pCO(2) gap in VO(2) non-responders only. The pCO(2) gap/C(a-v)O(2) ratio and C(a-v)CO(2) content /C(a-v)O(2) content ratio did not change with FC. The CO(2) gap content/C(a-v)O(2) content ratio and the C(a-v)CO(2) content /C(a-v)O(2) content ratio did not predict fluid-induced VO(2) changes (area under the curve (AUC) [95% confidence interval (CI)] = 0.52 [0.39‒0.64] and 0.53 [0.4–0.65], respectively; p = 0.757 and 0.71, respectively). ScvO(2) predicted an increase of more than 15% in the VO(2) (AUC [95%CI] = 0.67 [0.55‒0.78]; p<0.0001). CONCLUSIONS: Our results showed that the ratios of central venous to arterial carbon dioxide content and tension to arteriovenous oxygen content were not predictive of VO(2) changes following fluid challenge in postoperative cardiac surgery patients.